O Sistema Integrado de Gestão Policial – SIGPOL: o banco de dados da Polícia Militar do Estado do Pará - PINHEIRO, Kilson Leonez (2017)
The object of this study addresses the “Sistema Integrado de Gestão Policial” - SIGPOL implanted in the “Polícia Militar do Estado do Pará”, which aims to determine the organization and access to information in the “Sistema Integrado de Gestão Policial” - SIGPOL from “Polícia Militar do Estado do Pará”, as well the organization, advantages and disadvantages describing the data entry process of the militaries. Was realized a short research on the “1º Batalhão da Polícia Militar do Estado do Pará”, and as a tool for data collection a questionnaire, which was applied to a universe of a total of fifteen (15) police officers involved in the system. All military officers interviewed work in the same seat sections totaling 50% (fifty percent) of the effective officers that work in SIGPOL, the results were presented and discussed with demonstrations in the table and graphs completion is directed to improvement and solution of the initial problem in SIGPOL, leaving subsidies and projection for future research and expansions of knowledge that is related to SIGPOL as a provider and database which offers and makes available services oriented to informational area of any institution.